Handbook of HPLC - Corradini, Danilo. Ed (Chromatographic science series ;, 2010)
High performance liquid chromatography (HPLC) is one of the most widespread analytical and preparative scale separation techniques used for both scientific investigations and industrial and biomedical analysis. Now in its second edition, this revised and updated version of the Handbook of HPLC examines the new advances made in this field since the publication of the benchmark first edition twelve years ago. It reports detailed information on fundamental and practical aspects of HPLC related to conventional format and sophisticated novel approaches which have been developed to address a variety of separation problems in different fields.